Continuous‐Flow Synthesis of Supported Magnetic Iron Oxide Nanoparticles for Efficient Isoeugenol Conversion into Vanillin. Issue 2 (28th December 2017) - Marquez‐Medina, M. Dolores; Prinsen, Pepijn; Li, Hangkong; Shih, Kaimin; Romero, Antonio A.; Luque, Rafael
Abstract: This work presents the synthesis of iron oxide nanocatalysts supported on mesoporous Al‐SBA‐15 by using a continuous‐flow setup. The magnetic nanomaterials were tested as catalysts in the oxidative disruption of isoeugenol by using hydrogen peroxide as a green oxidant, featuring high activities (63–88 % conversion) and good selectivities to vanillin (44–68 %). The catalytic systems exhibited good magnetic properties when synthesized under continuous‐flow conditions at temperatures not exceeding 190 °C. The use of microwave irradiation significantly reduced times of reaction drastically but exerted negative effects on catalyst reusability. Abstract : Isoeugenol conversion into vanillin : Magnetic iron oxide nanoparticles supported on Al‐SBA‐15, prepared under continuous flow, are highly active and selective for the disruptive oxidation of isoeugenol to vanillin by using hydrogen peroxide as a green oxidant.